Evaluation of humidity sensing properties of TMBHPET thin film embedded with spinel cobalt ferrite nanoparticles - Zafar, Q.; Azmer, M.I.; Al-Sehemi, A.G.; Al-Assiri, M.S.; Kalam, A.; Sulaiman, K. (Kluwer (now part of Springer), 2016)
In this study, we report the enhanced sensing parameters of previously reported TMBHPET-based humidity sensor. Significant improved sensing performance has been demonstrated by coupling of TMBHPET moisture sensing thin film with cobalt ferrite nanoparticles (synthesized by eco-benign ultrasonic method). The mean size of CoFe2O4 nanoparticles has been estimated to be ~ 6.5 nm. It is assumed that the thin film of organic–ceramic hybrid matrix (TMBHPET:CoFe2O4) is a potential candidate for humidity sensing utility by virtue of its high specific surface area and porous surface morphology (as evident from TEM, FESEM, and AFM images). The hybrid suspension has been drop-cast onto the glass substrate with preliminary deposited coplanar aluminum electrodes separated by 40 µm distance. The influence of humidity on the capacitance of the hybrid humidity sensor (Al/TMBHPET:CoFe2O4/Al) has been investigated at three different frequencies of the AC applied voltage (Vrms ~ 1 V): 100 Hz, 1 kHz, and 10 kHz. It has been observed that at 100 Hz, under a humidity of 99 % RH, the capacitance of the sensor increased by 2.61 times, with respect to 30 % RH condition. The proposed sensor exhibits significantly improved sensitivity ~560 fF/ % RH at 100 Hz, which is nearly 7.5 times as high as that of pristine TMBHPET-based humidity sensor. Further, the capacitive sensor exhibits improved dynamic range (30–99 % RH), small hysteresis (~2.3 %), and relatively quicker response and recovery times (~12 s, 14 s, respectively). It is assumed that the humidity response of the sensor is associated with the diffusion kinetics of water vapors and doping of the semiconductor nanocomposite by water molecules.